Expression of PD‐L1, indoleamine 2, 3‐dioxygenase and the immune microenvironment in gastric adenocarcinoma. Issue 1 (17th April 2018) - Patil, Pallavi A; Blakely, Andrew M; Lombardo, Kara A; Machan, Jason T; Miner, Thomas J; Wang, Li‐Juan; Marwaha, Alexander S; Matoso, Andres
Abstract : Aims: The tumour microenvironment is increasingly important in several tumours. We studied the relationship of key players of immune microenvironment with clinicopathological parameters in gastric adenocarcinomas. Methods and results: Tissue microarrays were constructed from gastrectomy specimens, 2004–13. Immunohistochemistry was performed for programmed cell death ligand 1 (PD‐L1), indoleamine 2, 3‐dioxygenase (IDO), tryptophanyl‐tRNA synthetase (WARS), guanylate‐binding protein 5 (GBP5), tumour‐infiltrating lymphocytes (TIL) expressing CD3/CD8/FoxP3/PD1 and mismatch repair proteins (MMRs) MLH1, PMS2, MSH2 and MSH6. Clinicopathological parameters and clinical follow‐up were recorded. The study included 86 patients; median follow‐up was 34 months (0–148). Tumour types were 45% tubular, 38% diffuse, 17% mixed. PD‐L1 was positive in 70%, epithelial IDO in 58%, stromal IDO in 91%, epithelial WARS in 67%, stromal WARS in 100%, epithelial GBP5 in 53% and stromal GBP5 in 71%. MMR‐deficiency was found in 22%. There was no difference in biomarker expression by histological subtype, with the exception of fewer diffuse‐type being MMR‐deficient. Low stromal IDO was associated with decreased progression‐free, overall and disease‐specific survival. PD‐L1‐positive tumours were larger with MMR‐deficiency and with increasing TILs, and had significantly higher FoxP3TILs. Conclusions: PD‐L1 is expressed in a large proportion of gastric carcinomas, suggesting that therapy targeting this pathway could be relevant to many patients. PD‐L1 expression and MMR‐deficiency are associated with increased TILs and larger tumour size, emphasising their role in tumour biology. Higher stromal IDO expression is associated with better prognosis. Finally, we observed that immune modulators WARS and GBP5 are expressed highly in gastric adenocarcinomas, suggesting an important role in tumour pathobiology.